Evaluation of stereotactic radiotherapy of the resection cavity after surgery of brain metastases compared to postoperative whole-brain radiotherapy (ESTRON) - a single-center prospective randomized trial - El-Shafie, Rami; Paul, Angela; Bernhardt, Denise; Hauswald, Henrik; Welzel, Thomas; Sprave, Tetyana; Hommertgen, Adriane; Krisam, Johannes; Schmitt, Daniela; Klüter, Sebastian; Schubert, Kai; Klose, Christina; et al. (Neurosurgery, 2018)
AbstractBACKGROUND. Neurosurgical resection is recommended for symptomatic brain metastases, in oligometastatic patients or for histology acquisition. Without
Gesehen am 14.08.2019